Biodiversity and social aspects of the Sawo-Lahewa Marine Protected Area, North Nias: a social-ecological mapping. Issue 1 (October 2020) - Abdurrahim, A Y; Siringoringo, R M; Abrar, M; Triyono,; Sari, N W P
Abstract: Sawo-Lahewa sea waters, North Nias District, North Sumatra Province was determined to become one of the marine conservation areas on December 22, 2017 through the Decree of the Minister of Marine Affairs and Fisheries Republic of Indonesia Number 54/Kepmen-KP/2017. This stipulation aims to protect, preserve, and utilize the potential of fisheries and important habitats (coral reefs, mangroves, and seagrass) and important species (turtles, dolphins, manta rays, napoleons, lola, dugongs, whale sharks, sea bamboo Isis puridis, Black Coral Anthipatharia, etc.) to support tourism development. This paper aims to map the condition of biodiversity and social aspects in the Sawo-Lahewa Marine Conservation Area by using the social-ecological framework. Using the data on ecological and social conditions were collected during 2014-2015 and updated with 2019-2020 data. The mapping of ecological aspects have involved the condition of coastal-marine ecosystems, including coral reefs, reef fish abundance, reef megabentos abundance, mangroves, and seagrasses) and also oceanographic conditions, meanwhile, the mapping of social aspects including socio-demography and socio-economics aspects. To enrich the analysis, this paper is was also equipped with a discussion of zoning arrangements. Important findings from this study that the sustainability of biodiversity is influenced by the sustainability of local social activities; vice versa.